Earsplitters! : the world's loudest noises - Parker, Steve, 1952- (Mankato, Minn. : Capstone Press, 2008)
Presents the science behind sound including dragster races, rock concerts, and rockets.
Book Links (A.L.A.), June 2010
Includes bibliographical references (p. 31), filmography, and index.
4.8
3-6
Keywords: Noise -- Juvenile literature; Sounds -- Juvenile literature; Noise; Sounds; Noise; Sounds